GREEN SYNTHESIS OF ZINC OXIDE (ZNO) NANOPARTICLES USING KEPOK BANANA LEAF EXTRACT (Musa Paradisiaca L.) FOR METHYLENE BLUE DEGRADATION - Amrina Mustaqim; Vera Khoirunisa; Syamsyarief Baqaruzi; Nadia Soni Utami; Retno Maharsi (Universitas Mataram, 2026)
This study examines the effect of Musa paradisiaca L. leaf extract concentration (6%, 8%, and 10%) on the structural, morphological, and photocatalytic properties of ZnO nanoparticles synthesized via a green method, with a focus on methylene blue (MB) degradation. XRD analysis confirms the formation of ZnO with crystallite sizes in the range of 34–37 nm, while SEM observations show particle sizes of approximately 40–130 nm, indicating agglomeration. The results also show that increasing the extract concentration from 6% to 10% reduces the band gap energy from 3.24 eV to 3.05 eV, which is followed by an increase in MB degradation efficiency up to 78% after 180 minutes. This trend indicates a clear relationship between extract concentration, band gap energy, and photocatalytic activity, where a lower band gap enables more effective light absorption and enhances degradation performance. Overall, the findings demonstrate that extract concentration is a key parameter in improving the photocatalytic performance of ZnO nanoparticles for dye degradation.